Turning votes into victory points: politics in modern board games - Quasdorf, Torben (Gamevironments, 2020)
Board games are gaining in popularity as well as sophistication on a thematic and mechanical level. We need to understand the role of this medium within our culture at large, especially in areas where board games interact with fundamental cultural values like the idea of democracy. To further this understanding, I will apply Ian Bogost’s concept of procedural expression to board games and analyze two examples that allow me to cover a wide range of phenomena: Karl-Heinz Schmiel’s Die Macher, first published in 1986, and T. L. Simons’ Bloc by Bloc: The Insurrection Game, first published in 2016. The analysis will demonstrate how a game can represent its political theme on various levels and achieve a conflicting or a coherent political message. The example of Bloc by Bloc will prove that board games are capable of expressing very nuanced political positions and stimulating a critical reflection of our political culture and even the role that board games might play in it.